2011
DOI: 10.5194/acpd-11-30627-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The isotopic record of Northern Hemisphere atmospheric carbon monoxide since 1950, implications for the CO budget

Abstract: We present a 60-yr record of atmospheric CO concentration and stable isotopic ratios at high northern latitude based on firn air samples collected in the frame of the North Greenland Eemian Ice Drilling (NEEM) project. Concentration, δ<sup>13</sup>C, and δ<sup>18</sup>O of CO from trapped gases in the firn were measured by gas chromatography coupled with isotope ratio mass spectrometry (gc-IRMS). Using models of trace gas transport in firn, the long-term trend of atmospheric CO … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Paris shows a reduction in CO total column compared to 2000–2003 (−22%), while Delhi presents a large increase (+22.4%) (Table ). Over Europe as a whole, this decrease began with the invention (in 1975) and mandatory application (in 1993) of catalytic converters and the growth of diesel engine vehicle market share [ Wang et al ., ]. There may also be some connection to the 2008 economic crisis as explained by Castellanos and Boersma [], who observed a modification of the regional NO x concentrations due to changes in the economy in Europe, even if this crisis overlaps only the last year of our studied period.…”
Section: Changes In Megacity Co Emissionsmentioning
confidence: 99%
“…Paris shows a reduction in CO total column compared to 2000–2003 (−22%), while Delhi presents a large increase (+22.4%) (Table ). Over Europe as a whole, this decrease began with the invention (in 1975) and mandatory application (in 1993) of catalytic converters and the growth of diesel engine vehicle market share [ Wang et al ., ]. There may also be some connection to the 2008 economic crisis as explained by Castellanos and Boersma [], who observed a modification of the regional NO x concentrations due to changes in the economy in Europe, even if this crisis overlaps only the last year of our studied period.…”
Section: Changes In Megacity Co Emissionsmentioning
confidence: 99%
“…The net emission of CO to the atmosphere is the summed contribution from all distinct sources, including anthropogenic, biomass burning, biogenic, and ocean. We know that, in the past, variations in the relative amounts of these sources have changed over time, in both the short term—seasonal to interannual—[ Novelli et al ., ; Park and Rhee , ; Park et al ., ] and the long term—multidecadal to centennial [ Wang et al ., , ]. Briefly, Novelli et al .…”
Section: Introductionmentioning
confidence: 99%
“…[] reported that CO varied from 38 to 55 ppbv mainly due to the change in biomass burning CO. Also, Wang et al . [] found from the analysis of the past 60 year record of CO from the Greenland firn air samples that CO varied from 90 to 160 ppbv and that the fossil fuel source is the primary contribution to the observed CO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The d 13 C ratio of carbon monoxide in Well C-l0A (Table 3) falls in a narrow range from ¡41.19% to ¡43.29%. The d 13 C range in the atmosphere in the year 2000, is approximately in the range ¡31% to ¡22% (Wang et al, 2002). No CO was detected in the other two wells.…”
Section: Carbon Monoxidementioning
confidence: 96%